Mengembangkan Potensi Bisnis Dengan Dangkot Ayam Sebagai Produk Unggulan - Patangkin, Imelda; Yunita, Marwah; Nadila; Putri, Afika Sari; Azizah, Rafika; Rahmayanti; Mulyawati, Yayu; Sapar (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
The production and marketing process of dangkot chicken for all people is the goal of the Student Entrepreneurship Creativity Program (PKM-K) to stimulate students' motivation to start a business in processing the Toraja's signature dangkot chicken. The implementation method of this program includes input, process (production), output, and evaluation. The result of this program is to conduct a market survey to determine the market condition, followed by interviewing five female students in the Universitas Muhammadiyah Palopo environment, and then conducting a feasibility study on the business to be carried out. The last stage is the selection of materials and the provision of places and facilities to support the production process. The production process involves preparing the ingredients and tools until the dangkot is marketed. The output is the ready-to-consume dangkot chicken that is marketed to consumers. The final stage is evaluation, which is conducted after the dangkot chicken production is completed to review any shortcomings that make consumers uncomfortable with our products. In conclusion, the PKM-K program aims to keep the production and marketing process of Toraja's dangkot chicken innovative and creative, provide opportunities for students to practice entrepreneurship with a comprehensive understanding of entrepreneurship concepts, and build students' spirit to continue their business in the food industry, particularly in the Toraja's signature dangkot chicken business.